Solar cell and preparation method thereof

By combining N-type TOPCon cells and perovskite cell structures in solar cells, and employing a p+/p high-low junction design at the interface of high and low concentration boron doping regions, the problem of balancing efficiency and reliability in existing solar cells is solved, improving photoelectric conversion efficiency and reducing the impact of ultraviolet and infrared radiation.

CN120826099APending Publication Date: 2025-10-21DAS SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410433805.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing solar cells cannot effectively balance photoelectric conversion efficiency and reliability. The theoretical limit of N-type cell efficiency is 28.7%, while perovskite solar cells are sensitive to ultraviolet and infrared wavelengths, resulting in poor reliability.

Method used

A solar cell structure was designed, comprising, from front to back, a front fine grid, a first antireflection layer, a passivation layer, a boron-doped layer, an N-type silicon wafer, a tunneling oxide layer, a phosphorus-doped polycrystalline silicon layer, a second antireflection layer, a first conductive layer, a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer, and a back fine grid. A p+/p high-low junction is formed at the junction of the high-concentration boron-doped region and the low-concentration doped region. Combining the N-type TOPCon cell and the perovskite cell structure, the main grid is eliminated.

Benefits of technology

This method improves the photoelectric conversion efficiency of N-type TOPCon cells, reduces the impact of ultraviolet and infrared radiation on perovskite cells, increases the effective utilization area of ​​the cells, and achieves a balance between photoelectric conversion efficiency and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120826099A_ABST
    Figure CN120826099A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a solar cell and a preparation method thereof, and in the solar cell provided by the embodiment of the invention, a laminated perovskite cell structure is arranged on the back surface of an N-type TOPCon cell structure through connection of a first conductive layer, and high-concentration doping is carried out on a boron doped region in contact with a fine grid on the front surface of the N-type TOPCon cell structure, so that the conductivity of the solar cell is improved. The N-type TOPCon solar cell has the advantages that the N-type TOPCon solar cell is simple in structure, a main grid is omitted, the advantage of small attenuation of the N-type TOPCon solar cell can be guaranteed, the photoelectric conversion efficiency of the N-type TOPCon solar cell is improved, the influence of ultraviolet and infrared rays on the perovskite solar cell can be effectively reduced, the effect of high photoelectric conversion efficiency of the perovskite solar cell structure is achieved, the effective utilization area of a solar cell piece is increased, and the production cost is reduced. Therefore, the formed solar cell effectively gives consideration to photoelectric conversion efficiency and reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cell manufacturing, and in particular to a solar cell based on an N-type TOPCon cell and a perovskite cell and a preparation method thereof. Background Art

[0002] Currently, TOPCon cells among crystalline silicon solar cells are widely used due to their advantages such as low attenuation and obvious advantages in power generation; while perovskite solar cells (Perovskite Solar Cell) are a new type of solar cell technology that has attracted much attention for its advantages such as high efficiency, low cost and easy preparation.

[0003] However, the theoretical efficiency limit of N-type cells is only 28.7%. Although perovskite solar cells have a higher efficiency (the highest efficiency of multi-junction perovskite solar cells reaches 45%), perovskites are particularly sensitive to ultraviolet and infrared wavelengths, resulting in poor reliability of perovskite cells. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a solar cell and a preparation method thereof, so as to solve the problem that the existing solar cells cannot effectively take into account both photoelectric conversion efficiency and reliability.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides a solar cell, comprising a first welding ribbon, a solar cell, and a second welding ribbon; the solar cell comprises, from the front side to the back side, a front fine grid, a first anti-reflection layer, a passivation layer, a boron-doped layer, an N-type silicon wafer, a tunneling oxide layer, a phosphorus-doped polysilicon layer, a second anti-reflection layer, a first conductive layer, a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer, and a back fine grid, the front fine grid being in contact with the boron-doped layer and welded to the first welding ribbon, the first conductive layer being in contact with the phosphorus-doped polysilicon layer, and the back fine grid being welded to the second welding ribbon;

[0007] The boron-doped layer includes a first boron-doped region and a second boron-doped region. The first boron-doped region is used to contact the front fine gate. The second boron-doped region is other regions in the boron-doped layer except the first boron-doped region. The boron doping concentration of the first boron-doped region is higher than the boron doping concentration of the second boron-doped region.

[0008] Furthermore, in the solar cell, the first passivation layer includes an aluminum oxide layer, and the first anti-reflection layer and the second anti-reflection layer include silicon nitride layers.

[0009] Furthermore, in the solar cell, the first conductive layer and the second conductive layer are both indium oxide layers; and / or

[0010] The conductive transition layer is a zinc oxide layer; and / or

[0011] The hole transport layer comprises NiO and PVK; and / or

[0012] The material of the perovskite layer is CH3NH3PbCl3; and / or

[0013] The material of the electron transport layer is C60.

[0014] Furthermore, in the solar cell, the thickness of the first conductive layer is 160 to 210 nm; and / or

[0015] The thickness of the second conductive layer is 220-280 nm; and / or

[0016] The thickness of the conductive transition layer is 100 to 150 nm; and / or

[0017] The thickness of the hole transport layer is 20 to 30 nm; and / or

[0018] The thickness of the perovskite layer is 200 to 500 nm; and / or

[0019] The thickness of the electron transport layer is 20 to 50 nm.

[0020] The present invention provides a method for preparing a solar cell, which comprises:

[0021] After performing boron diffusion and laser doping on the front side of an N-type silicon wafer and sequentially forming a tunneling oxide layer and a phosphorus-doped polysilicon layer on the back side, a passivation layer is formed on the front side of the silicon wafer, and an anti-reflection layer is formed on the front side of the silicon wafer and on the surface of the phosphorus-doped polysilicon layer;

[0022] Printing laser-induced silver paste on the front surface to form a front fine grid, wherein the laser-induced silver paste comprises components including organic additives, silver powder, organic binder and glass powder;

[0023] The silicon wafer with the front and back fine grids formed thereon is subjected to light injection treatment, and the front fine grid of the silicon wafer after the light injection treatment is subjected to laser irradiation and deflection voltage treatment, wherein the direction of the electric field formed by the deflection voltage is opposite to the direction of the electric field built into the silicon wafer;

[0024] After laser irradiation and deflection voltage treatment, a first conductive layer conductive to the phosphorus-doped polysilicon layer is deposited on the back surface, and a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer and a back fine grid are sequentially formed on the first conductive layer;

[0025] The front fine grid is welded to a first welding strip, and the back fine grid is welded to a second welding strip to manufacture a solar cell.

[0026] Furthermore, before sequentially forming the tunneling oxide layer and the phosphorus-doped polysilicon layer on the back side, the preparation method further includes:

[0027] The silicon wafer after the laser doping treatment is subjected to oxidation annealing treatment.

[0028] Furthermore, in the laser-induced silver paste, the mass percentage of the organic additive is 1 to 1.5%; the mass percentage of the silver powder is 75 to 81%; the mass percentage of the organic binder is 15.3 to 22.2%; and the mass percentage of the glass powder is 1.8 to 2.2%.

[0029] Furthermore, in the preparation method, forming the back side fine grid specifically includes:

[0030] A low-temperature conductive silver paste is printed on the second conductive layer.

[0031] Furthermore, in the preparation method, during the light injection process, the light intensity is 5000-8000 W / m 2 .

[0032] Furthermore, in the preparation method, during the laser irradiation and deflection voltage treatment, the laser power is 10 to 15 W, the voltage intensity is 30 to 60 V, and the application time is 0.2 to 0.5 s.

[0033] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0034] In an embodiment of the present invention, a solar cell provided includes a first welding ribbon, a solar cell and a second welding ribbon. The solar cell includes, from the front to the back, a stacked front fine grid, a first anti-reflection layer, a passivation layer, a boron-doped layer, an N-type silicon wafer, a tunneling oxide layer, a phosphorus-doped polysilicon layer, a second anti-reflection layer, a first conductive layer, a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer and a back fine grid. The front fine grid contacts the boron-doped layer and is welded to the first welding ribbon. The first conductive layer contacts the phosphorus-doped polysilicon layer. The back fine grid is welded to the second welding ribbon. The boron-doped layer includes a first boron-doped region and a second boron-doped region. The first boron-doped region is used to contact the front fine grid. The second boron-doped region is the other region in the boron-doped layer except the first boron-doped region. The boron doping concentration of the first boron-doped region is higher than the boron doping concentration of the second boron-doped region. Through the connection of the first conductive layer, the stacked perovskite cell structure is set on the back of the N-type TOPCon cell structure, and the boron-doped area in contact with the fine grid on the front of the N-type TOPCon cell structure is doped with a high concentration, and the main grid is omitted. This not only ensures the advantage of the smaller attenuation of the N-type TOPCon cell and improves the photoelectric conversion efficiency of the N-type TOPCon cell, but also effectively reduces the impact of ultraviolet and infrared on the perovskite cell, and achieves the effect of higher photoelectric conversion efficiency of the perovskite cell structure, and increases the effective utilization area of ​​the cell, so that the formed solar cell effectively takes into account both photoelectric conversion efficiency and reliability.

[0035] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a schematic diagram of the structure of a solar cell provided by an embodiment of the present invention;

[0037] Figure 2 It is a flow chart of a method for preparing a solar cell provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0039] Currently, TOPCon cells among crystalline silicon solar cells are widely used due to their advantages such as low attenuation and obvious advantages in power generation; while perovskite solar cells (Perovskite Solar Cell) are a new type of solar cell technology that has attracted much attention for its advantages such as high efficiency, low cost and easy preparation.

[0040] The applicant of the present invention found that the theoretical efficiency limit of N-type cell is only 28.7%. Although perovskite solar cells have a higher efficiency (the highest efficiency of multi-junction perovskite solar cells reaches 45%), perovskite is particularly sensitive to ultraviolet and infrared wavelengths, resulting in poor reliability of perovskite cells.

[0041] In order to solve the above problems, the embodiment of the present invention provides a solar cell, such as Figure 1 As shown, it includes a first welding ribbon 30, a solar cell 10 and a second welding ribbon 40;

[0042] The solar cell includes, from the front to the back, a stacked front fine grid 11, a first anti-reflection layer 12, a passivation layer 13, a boron-doped layer 14, an N-type silicon wafer 15, a tunneling oxide layer 16, a phosphorus-doped polysilicon layer 17, a second anti-reflection layer 18, a first conductive layer 19, a hole transport layer 20, a perovskite layer 21, an electron transport layer 22, a conductive transition layer 23, a second conductive layer 24, and a back fine grid 25. The front fine grid 11 contacts the boron-doped layer 14 and is welded to the first welding ribbon 30. The first conductive layer 19 contacts the phosphorus-doped polysilicon layer 17. The back fine grid 25 is welded to the second welding ribbon 40.

[0043] The boron-doped layer 14 includes a first boron-doped region 141 and a second boron-doped region 142. The first boron-doped region 141 is used to contact the front fine gate 11. The second boron-doped region 142 is the other region in the boron-doped layer 14 except the first boron-doped region 141. The boron doping concentration of the first boron-doped region 141 is higher than the boron doping concentration of the second boron-doped region 142.

[0044] In an embodiment of the present invention, the front fine grid contacts the boron-doped layer to achieve conduction, the front fine grid is directly welded to the first welding ribbon to achieve current collection and series welding effects, and the first conductive layer contacts the phosphorus-doped polysilicon layer to achieve conduction; and the first anti-reflection layer, passivation layer, boron-doped layer, N-type silicon wafer, tunneling oxide layer, phosphorus-doped polysilicon layer, second anti-reflection layer, first conductive layer, hole transport layer, perovskite layer, electron transport layer, conductive transition layer, second conductive layer and back fine grid are contacted in sequence, and the back fine grid is directly welded to the second welding ribbon to achieve current collection and series welding effects, wherein the passivation layer covers other areas of the front side of the boron-doped layer except the front fine grid, and the first anti-reflection layer covers the passivation layer, thereby achieving a dielectric isolation effect on the front side of the N-type silicon wafer.

[0045] In an embodiment of the present invention, the boron doping concentration of the first boron doping region in the boron doping layer is higher than the boron doping concentration of the second boron doping region, that is, high-concentration doping is performed in the electrode region, and low-concentration light doping is performed in the light absorption region. In this way, a lateral p+ / p high-low junction can be obtained at the junction of the lightly doped region and the highly doped region, and a p+ / n junction can be obtained under the electrode gate line. This structure can reduce the emitter contact resistance and the dark saturation current of the emitter region, improve the fill factor, short-circuit current and open-circuit voltage, thereby improving the conversion efficiency of the battery.

[0046] Because the front fine grid 11, the first anti-reflection layer 12, the passivation layer 13, the boron-doped layer 14, the N-type silicon wafer 15, the tunneling oxide layer 16, the phosphorus-doped polysilicon layer 17, the second anti-reflection layer 18, and the first conductive layer 19 together constitute the N-type TOPCon cell structure, and the first conductive layer 19, the hole transport layer 20, the perovskite layer 21, the electron transport layer 22, the conductive transition layer 23, the second conductive layer 24 and the back fine grid 25 together constitute the perovskite cell structure, the solar cell provided in the embodiment of the present invention combines the N-type TOPCon cell structure and the perovskite cell structure; because through the first conductive The electrical layer is connected, the stacked perovskite cell structure is set on the back of the N-type TOPCon cell structure, and the boron-doped area in contact with the fine grid on the front of the N-type TOPCon cell structure is doped with a high concentration, and the main grid is omitted. This not only ensures the advantage of smaller attenuation of the N-type TOPCon cell and improves the photoelectric conversion efficiency of the N-type TOPCon cell, but also effectively reduces the impact of ultraviolet and infrared on the perovskite cell, and achieves the effect of higher photoelectric conversion efficiency of the perovskite cell structure, and increases the effective utilization area of ​​the cell, so that the formed solar cell effectively takes into account both photoelectric conversion efficiency and reliability.

[0047] Optionally, a projection of the front fine gate is within the first boron-doped region.

[0048] Optionally, the boron doping concentration of the first boron doping region is 1E19-2E19 / cm 3 The boron doping concentration of the second boron doping region is 2E18~4E18 / cm 3 .

[0049] Optionally, the square resistance of the second boron-doped region is 220 to 280 Ω / sq, for example, it can be a range value between one or both of 220 Ω / sq, 250 Ω / sq, and 280 Ω / sq, and the junction depth of the second boron-doped region is 0.6 to 0.8 μm, for example, it can be a range value between one or both of 0.6 μm, 0.65 μm, and 0.8 μm; the square resistance of the first boron-doped region is 100 to 150 Ω / sq, for example, it can be a range value between one or both of 100 Ω / sq, 140 Ω / sq, and 150 Ω / sq, and the junction depth of the first boron-doped region is 0.9 to 1.2 μm, for example, it can be a range value between one or both of 0.9 μm, 1.05 μm, and 1.2 μm.

[0050] Optionally, the front fine grid may be formed by laser-induced silver paste, and the components constituting the laser-induced silver paste include organic additives, silver powder, organic adhesive and glass powder.

[0051] Optionally, in the laser-induced silver paste, the mass percentage of organic additives is 0.8-1.2%, the mass percentage of silver powder is 75-83%, the mass percentage of organic binder is 13.3-22.2%; and the mass percentage of glass powder is 2-2.5%, which can better match the light injection and laser induction effects and improve the photoelectric conversion efficiency of the battery.

[0052] Optionally, the first passivation layer includes an aluminum oxide layer, and the first anti-reflection layer and the second anti-reflection layer include silicon nitride layers.

[0053] The tunnel oxide layer may be a silicon dioxide layer with a thickness of 1 to 4 nm, for example, 1 nm, 2.5 nm, 4 nm, or any combination thereof. The thickness of the first and second anti-reflection layers may be 75 to 80 nm.

[0054] The thickness of the phosphorus-doped polysilicon layer may specifically be 90-150 nm, for example, may be in the range of 90 nm, 110 nm, 150 nm, or a value in between.

[0055] Optionally, the first conductive layer and the second conductive layer are both indium oxide layers, that is, made of indium oxide; wherein the thickness of the first conductive layer is 160 to 210 nm, for example, it can be a range value between one of 160 nm, 180 nm, 210 nm or a range value between the two; the thickness of the second conductive layer is 220 to 280 nm, for example, it can be a range value between one of 210 nm, 250 nm, 280 nm or a range value between the two.

[0056] Optionally, the conductive transition layer is a zinc oxide layer, that is, the dense conductive transition layer is made of zinc oxide, and the thickness of the conductive transition layer is 100 to 150 nm, for example, it can be one of 100 nm, 120 nm, 150 nm or a range between the two.

[0057] Optionally, the hole transport layer comprises NiO and PVK, that is, the hole transport layer is made of NiO and PVK; the thickness of the hole transport layer is 20 to 30 nm, for example, it can be one of 20 nm, 25 nm, 30 nm or a range between the two.

[0058] Optionally, the material of the perovskite layer is CH3NH3PbCl3; the thickness of the perovskite layer is 200-500 nm, for example, it can be a range of one of 200 nm, 350 nm, 500 nm, or a value in between.

[0059] Optionally, the material of the electron transport layer is C60, that is, the electron transport layer is made of C60; the thickness of the electron transport layer is 20 to 50 nm, for example, it can be one of 20 nm, 35 nm, 50 nm or a range value between the two.

[0060] In an embodiment of the present invention, the back-side fine grid is made of a low-temperature conductive silver paste. The low-temperature conductive silver paste comprises 83-87 wt% silver powder, 1-5 wt% glass powder, and 10-14 wt% organic matter. The paste can be dried at 300-400°C to avoid damage to the perovskite cell caused by high-temperature baking. It is also suitable for contact with the second conductive layer, ITO.

[0061] In practical applications, the solar cell provided by the embodiment of the present invention also includes a cover glass arranged on the front of the solar cell and a back plate arranged on the back of the solar cell; the solar cell includes a plurality of the above-mentioned solar cells, and the plurality of the above-mentioned solar cells are welded in series through the first welding ribbon and the second welding ribbon as mentioned above to form a cell string.

[0062] Optionally, the above-mentioned solar cell also includes a front adhesive film and a back adhesive film; the front adhesive film is arranged between the cover glass and the solar cell, and is used to bond the cover glass and the solar cell; the back adhesive film is arranged between the solar cell and the back panel, and is used to bond the solar cell and the back panel.

[0063] Optionally, in the solar cell, the front adhesive film and the back adhesive film are both POE films.

[0064] In order to solve the above problems, the present invention also provides a method for preparing a solar cell. Figure 2 As shown, it includes steps 201 to 205:

[0065] Step 201: After boron diffusion and laser doping are performed on the front side of an N-type silicon wafer and a tunneling oxide layer and a phosphorus-doped polysilicon layer are sequentially formed on the back side, a passivation layer is formed on the front side of the silicon wafer, and an anti-reflection layer is formed on the front side of the silicon wafer and on the surface of the phosphorus-doped polysilicon layer.

[0066] In the above step 201, boron diffusion treatment is performed on the front side of the silicon wafer, and then a laser doping (SE) process is performed, wherein the SE image is screen-printed on the front fine grid screen to perform high-concentration doping on the front fine grid area. The principle of the SE laser BSG doping method is as follows: after boron diffusion on the N-type silicon wafer, a boron-rich borosilicate glass (BSG) layer is formed on the surface of the silicon wafer. The SE laser emitter uses this boron-rich BSG layer as a doping source and emits laser pulses at a high frequency to melt the surface of the silicon wafer, so that the boron atoms in the BSG layer are pushed to the surface of the silicon wafer. After the doped boron atoms solidify, they will quickly replace the position of the silicon atoms, thereby achieving the purpose of diffusion and advancement of the doped atoms.

[0067] Among them, the square resistance of the N-type silicon wafer surface after boron diffusion is 220~280Ω / sq, for example, it can be a range of one or two of 220Ω / sq, 250Ω / sq, 280Ω / sq, and the junction depth is 0.6~0.8μm, for example, it can be a range of one or two of 0.6μm, 0.7μm, 0.8μm; and the square resistance of the silicon wafer after SE is 100~150Ω / sq.

[0068] In the above step 201, low pressure chemical vapor deposition (LPCVD) technology is used to first prepare an ultra-thin silicon dioxide layer on the back of the battery as the above-mentioned tunneling oxide layer, and then a polycrystalline silicon thin layer is deposited on the ultra-thin silicon dioxide layer to form a passivation contact structure, wherein the thickness of the ultra-thin silicon dioxide layer is 1 to 4 nm and the thickness of the polycrystalline silicon thin layer is 90 to 150 nm. Then, the polycrystalline silicon thin layer is phosphorus-doped using tubular thermal decomposition POCl3 technology to form a battery passivation contact structure and carrier selective passage, thereby reducing battery surface recombination and metal contact resistance.

[0069] Optionally, in one embodiment, boron diffusion treatment is performed on the front side of the N-type silicon wafer at a temperature of 800-1100° C., a BCl3 flow rate of 200-500 sccm, an oxygen flow rate of 700-900 sccm / min, a nitrogen flow rate of 1500-5000 sccm / min, and a pressure of 120-180 mbar for deposition for 5-10 minutes.

[0070] In this embodiment, the silicon wafer is heated at a heating rate of 200 to 250°C / s, and then the silicon wafer is subjected to boron deposition at a temperature of 603 to 1100°C. The entire deposition process is controlled to take 5 to 30 minutes, so that the boron diffusion process of the silicon wafer can be completed quickly.

[0071] Optionally, in a specific embodiment, the method provided by the embodiment of the present invention further includes, before sequentially forming the tunneling oxide layer and the phosphorus-doped polysilicon layer on the back surface:

[0072] The silicon wafer after the laser doping treatment is subjected to oxidation annealing treatment.

[0073] In this specific embodiment, the laser-doped silicon wafer undergoes a push-in oxidation process at a temperature of 450-900°C to redistribute the diffused boron and form an oxide layer that protects the textured surface during alkaline polishing. For example, the push-in oxidation process is performed at a temperature of 450°C and an O2 flow rate of 3000 sccm for 6-10 minutes.

[0074] Among them, after the oxidation annealing treatment, the square resistance of the SE area on the front side of the silicon wafer is 100~150Ω / sq, for example, it can be a range value between one or two of 100Ω / sq, 140Ω / sq, 150Ω / sq, and the junction depth is 0.9~1.2μm, for example, it can be a range value between one or two of 0.9μm, 1.05μm, 1.2μm.

[0075] Optionally, in one embodiment, the phosphorus doping treatment of the polysilicon layer includes: depositing the phosphorus on the silicon wafer for 8 to 14 minutes at a temperature of 880 to 950° C., a phosphorus source including POCl3 and a flow rate of 120 to 150 sccm / min, an oxygen flow rate of 600 to 800 sccm / min, a nitrogen flow rate of 1400 to 2400 sccm / min, and a pressure of 160 to 190 mbar; then heating the silicon wafer to 950 to 1050° C., controlling the pressure to 920 mbar and the oxygen flow rate to 8000 to 14000 sccm / min for 40 to 65 minutes, and obtaining a surface doping concentration of 3E18 to 6E18 / cm 3 .

[0076] Among them, the square resistance of the phosphorus-doped polysilicon layer obtained after the phosphorus doping treatment is 30 to 40Ω / sq, for example, it can be a range value between one or two of 30Ω / sq, 38Ω / sq, and 40Ω / sq, and the junction depth is 1.1 to 1.2μm, for example, it can be a range value between one or two of 1.1μm, 1.15μm, and 1.2μm.

[0077] In the above step 201, an atomic layer deposition (ALD) process is used to plate a passivation layer on the entire front side of the product to form field passivation. After the passivation layer is formed, an anti-reflection layer can be plated on the front side of the battery and then on the back side to further enhance the passivation effect of the battery cell.

[0078] Alternatively, the passivation layer may be an aluminum oxide layer with a thickness of 3 to 5 nm. The ALD process temperature is 200 to 300° C., and the deposition time is 8 to 10 minutes. Cyclic deposition may be performed 10 times under the conditions of a TMA flow rate of 1500 sccm, an oxygen flow rate of 1800 sccm, and a temperature of 300° C., for a deposition time of 9 minutes.

[0079] Optionally, the anti-reflection layer may be SiN x Specifically, SiN can be deposited on the front and back of the battery using PECVD technology. x The anti-reflection layer is deposited at a thickness of 75 to 80 nm at a PECVD process temperature of 500 to 600°C for 4 to 6 minutes. The anti-reflection layer can passivate dangling bonds within the cell and enhance the reflection of incident light. For example, the deposition time can be 6 minutes at a silane flow rate of 1400 sccm, an ammonia flow rate of 400 sccm, a NO2 flow rate of 10,000 sccm, a pressure of 1500 Pa, a temperature of 500°C, and a power of 2100 W.

[0080] Step 202: Printing laser-induced silver paste on the front surface to form a front fine grid, wherein the laser-induced silver paste comprises components including organic additives, silver powder, organic adhesive and glass powder.

[0081] In the above step 202, after the anti-reflection layer is formed on the front and back surfaces, a metallic silver paste composed of an organic additive, silver powder, an organic adhesive and glass powder is used as the front metallization paste, and the front fine grid is screen-printed using the OBB technology and sintered and annealed at 500-850°C to prepare the above-mentioned front fine grid of the battery.

[0082] Among them, silver powder is the main component, which has good thermal conductivity, electrical conductivity and burn-through performance; glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; organic adhesive can ensure the overall bonding effect; organic additives can reduce the overall viscosity of silver paste; the above silver paste does not contain aluminum powder, and glass powder does not contain lead, which can avoid problems such as increased metal composites and reduced battery opening voltage caused by aluminum powder.

[0083] In the above step 202, the silver paste is solidified by high temperature sintering, and the silver paste is used to burn through the above passivation layer on the front side of the silicon wafer to form a front gate line in contact with the boron doped region after laser doping.

[0084] Step 203: perform light injection treatment on the silicon wafer with the front and back fine grids, and perform laser irradiation and deflection voltage treatment on the front fine grid of the silicon wafer after the light injection treatment, wherein the electric field direction formed by the deflection voltage is opposite to the electric field direction of the built-in electric field of the silicon wafer.

[0085] In the above step 203, the printed and sintered cell is subjected to light injection treatment to utilize photon energy to excite carriers in the semiconductor to achieve the basis of photoelectric conversion. Optionally, during the light injection treatment, the temperature is 500-600°C and the light intensity is 5000-8000W / m 2 .

[0086] In the above step 203, the fine grid on the front side of the silicon wafer after the light injection treatment is subjected to laser irradiation and deflection voltage treatment, and the current generated by the laser is transmitted along the low contact resistance path, inducing silver-silicon interdiffusion, thereby significantly reducing the contact resistance; wherein, the duration of the laser irradiation process matches the carrier lifetime, and the laser is quickly stopped after the laser, thereby achieving maximum retention of the original passivation layer and avoiding carrier recombination caused by direct contact between the metal and the silicon substrate.

[0087] Optionally, in the above light injection process, the temperature can be 500°C, 526°C, 600°C or a range between the two; the light intensity can be 5000W / m 2 、6500W / m 2 , 8000W / m 2 One or both of the range of values ​​between.

[0088] Optionally, in a specific embodiment, during the laser irradiation and deflection voltage treatment, the laser power is 10-15W, the voltage intensity is 30-60V, and the application time is 0.2-0.5s. In this specific embodiment, the laser intensity, voltage intensity, and application time are reasonably matched with the silver paste, which can effectively reduce the contact resistance between the front fine grid and the silicon wafer while maintaining the original passivation layer, and achieve a doping effect similar to that of aluminum-containing silver paste, thereby achieving a doping effect similar to that of aluminum-containing silver paste without the aluminum powder.

[0089] Step 204: After laser irradiation and deflection voltage treatment, a first conductive layer that is conductive to the phosphorus-doped polysilicon layer is deposited on the back of the cell, and a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer and a back fine grid are sequentially formed on the first conductive layer.

[0090] In the above step 204, the laser-induced cell is grooved to partially expose the phosphorus-doped polysilicon layer, and then a first conductive layer is deposited on the entire back side of the cell so that the first conductive layer can be conductive with the phosphorus-doped polysilicon layer. Then, a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer and a back fine grid are sequentially formed on the back side of the first conductive layer to produce a solar cell.

[0091] The phosphorus-doped polysilicon layer can be partially exposed by laser grooving, and the grooving depth is just enough to destroy the silicon nitride film on the back side, for example, 120 nm, which does not affect the phosphorus-doped polysilicon layer of the LP process.

[0092] Among them, the first conductive layer can be an indium oxide layer. Take the battery cell after the groove is formed, and deposit ITO on the back of the groove to form the above-mentioned first conductive layer; then prepare a layer of NiO and PVK on the prepared first conductive layer to form a hole transport layer; then prepare a layer of CH3NH3PbCl3 on the prepared hole transport layer to form a perovskite layer; prepare a layer of C60 as an electron transport layer by thermal evaporation on the prepared perovskite layer; deposit a layer of dense ZnO as a conductive transition layer by atomic layer deposition, and then deposit ITO on the conductive transition layer to form a second conductive layer, and finally use the screen printing method to print the back fine grid on the second conductive layer.

[0093] Among them, the thickness of the first conductive layer is 160 to 210 nm, for example, it can be a range value between one of 160 nm, 280 nm, and 210 nm or a range value between the two; the thickness of the second conductive layer is 220 to 280 nm, for example, it can be a range value between one of 220 nm, 250 nm, and 280 nm or a range value between the two; the thickness of the conductive transition layer is 100 to 150 nm, for example, it can be a range value between one of 100 nm, 120 nm, and 150 nm or a range value between the two; the thickness of the hole transport layer is 20 to 30 nm, for example, it can be a range value between one of 20 nm, 25 nm, and 30 nm or a range value between the two; the thickness of the perovskite layer is 200 to 500 nm, for example, it can be a range value between one of 200 nm, 300 nm, and 500 nm or a range value between the two; the thickness of the electron transport layer is 20 to 50 nm, for example, it can be a range value between one of 20 nm, 25 nm, and 50 nm or a range value between the two.

[0094] Alternatively, magnetron sputtering equipment may be used to deposit ITO to form the first conductive layer and the second conductive layer. Optionally, during the magnetron sputtering process, a magnetic field may be applied to increase the ion density in the gas, thereby improving the uniformity and quality of the thin film.

[0095] Among them, during the magnetron sputtering process, the RF power can be set to 12.6MHZ, and the target material is ITO; the target material is sintered by 85wt% In2O3 and 15wt% SnO2, and the flow rate of oxygen and argon is 180sccm under the condition of vacuum 8E-4 Pa, and the RF is started when the gas pressure reaches 0.3 Pa.

[0096] Before preparing the perovskite layer, it is soaked in an organic solvent such as ethanol or isopropanol and ultrasonically cleaned, and then blown dry with nitrogen;

[0097] The temperature for depositing the CH3NH3PbI3 perovskite layer is between 80℃ and 150℃. The substrate and evaporation source can be heated by a heat source or flowing gas. The evaporation rate is controlled between arrive to ensure uniform film deposition; the temperature of the evaporation source is controlled between 100°C and 200°C to adjust the evaporation rate and composition of the material; during the preparation process, the CH3NH3PbI3 perovskite layer is evaporated under an inert gas (such as nitrogen) or a controlled atmosphere (such as chlorine or iodine), and the thickness of the film can be controlled by adjusting the evaporation time.

[0098] Before preparing the electron transport layer by thermal evaporation, the film is soaked in an organic solvent such as ethanol or isopropanol and ultrasonically cleaned, and then dried with nitrogen. The thermal evaporation temperature is between 150°C and 500°C, and the evaporation rate is controlled between arrive To ensure uniform film deposition, evaporation is performed under an inert gas (such as nitrogen) or a controlled atmosphere (such as chlorine or iodine), and the thickness of the film can be controlled by adjusting the evaporation time.

[0099] The process of forming the conductive transition layer specifically includes:

[0100] Repeat steps 1 to 4 six times:

[0101] Step 1: introducing H2O at a flow rate of 2800 sccm at a temperature of 250°C for a duration of 6 seconds;

[0102] Step 2: Wait for 6 seconds.

[0103] Step 3: introducing trimethylzinc and H2O at a flow rate of 2800 sccm each for 8 seconds;

[0104] Step 4: Wait 8 seconds to start cooling.

[0105] Optionally, in one embodiment, forming the back side fine grid specifically includes:

[0106] A low-temperature conductive silver paste is printed on the second conductive layer.

[0107] In the above embodiment, the low-temperature conductive silver paste includes 83-87 wt% silver powder, 1-5 wt% glass powder, and 10-14 wt% organic matter by mass. It can be dried at a low temperature of 300-400°C to avoid damage to the perovskite cell caused by high-temperature baking, and is also suitable for contact with the second conductive layer ITO.

[0108] Step 205: Weld the front fine grid to the first welding ribbon, and weld the back fine grid to the second welding ribbon to manufacture a solar cell.

[0109] In this step, the first welding strip is directly welded to the front fine grid, and the second welding strip is welded to the back fine grid, thereby eliminating the main grid and achieving current collection and series welding effects.

[0110] In the preparation method provided by the embodiment of the present invention, laser doping is performed after boron diffusion of the N-type silicon wafer, and aluminum powder is omitted in the silver paste for forming the front grid line. Laser induction is performed after light injection, which can trigger silver-silicon interdiffusion, thereby significantly reducing contact resistance, improving the fill factor of the battery, and effectively improving the efficiency of the battery cell. At the same time, using the first conductive layer as the connection interface, a perovskite cell structure is stacked on the back side of the N-type silicon wafer, which not only ensures the advantage of smaller attenuation of the N-type TOPCon cell, but also effectively reduces the influence of ultraviolet and infrared on the perovskite cell, and achieves the effect of higher photoelectric conversion efficiency of the perovskite cell structure. By omitting the main grid, the effective utilization area of ​​the cell is increased, so that the formed solar cell effectively takes into account both photoelectric conversion efficiency and reliability.

[0111] In the above step 201, the above silicon wafer is an N-type silicon wafer after texturing. Through the texturing process, a double-surface pyramid structure can be formed on the silicon wafer.

[0112] Optionally, in one embodiment, before the above step 201, step 200 is further included:

[0113] Step 200: Place the N-type silicon wafer into a texturing tank for single crystal alkaline texturing.

[0114] In this embodiment, an alkali texturing treatment is performed to remove the mechanical damage layer and metal ions on the surface of the single crystal N-type original silicon wafer, and a "pyramid" appearance is formed on the surface of the battery, thereby improving the light trapping effect of the battery.

[0115] Among them, the texturing liquid in the texturing tank mainly includes acid and alkali solutions, and the single crystal alkali texturing specifically includes: first using alkali solution for alkali texturing, and then using acid solution for pickling; wherein, the alkali solution includes NaOH or KOH, and the solution mass fraction is 0.5~1.2%; the acid solution is HCL or HF, and the solution mass fraction is 0.5~1.2%; the above-mentioned single crystal alkali texturing time is between 550~650s, and the corresponding weight loss is 0.2~0.4g, and the tested suede surface reflectivity can be around 9.15%.

[0116] Optionally, in one embodiment, the method provided in an embodiment of the present invention further includes step 2011 after performing boron diffusion treatment on the front side of the N-type silicon wafer and before sequentially forming the tunneling oxide layer and the phosphorus-doped polysilicon layer on the back side:

[0117] Chain pickling is used to remove the borosilicate glass layer on the back of the silicon wafer, and then alkaline polishing is performed.

[0118] In this embodiment, since boron diffusion only needs to be performed on the front side of the silicon wafer, single-sided diffusion is required. The borosilicate glass layer formed on the back side of the non-diffused surface is removed by chain pickling, and the silicon wafer is alkaline polished using a high-concentration alkaline solution to form a block-sized morphology structure, forming a polished surface with high reflectivity, thereby improving the surface flatness of the battery, increasing the reflection of long-wave light, promoting secondary absorption of light, increasing short-circuit current and reducing leakage current.

[0119] Optionally, the acidic solution in the chain pickling is HF and / or HCl with a mass concentration of 1-3%, the alkaline solution is NaOH or KOH with a mass concentration of 5-10%, the alkali polishing reaction time is between 280-300s, and the treatment temperature is 60-70°C, which can effectively improve the surface flatness of the battery, increase the reflection of long-wave light, promote the secondary absorption of light, increase the short-circuit current and reduce the leakage current.

[0120] Optionally, in one embodiment, the method provided in the embodiment of the present invention further includes step 2012 before forming the passivation layer on the front surface of the silicon wafer and the surface of the phosphorus-doped polysilicon layer:

[0121] Chain pickling is used to remove the phosphosilicate glass layer on the front of the silicon wafer, and then alkaline polishing is performed.

[0122] In this embodiment, because phosphorus doping is performed using a furnace tube, a phosphosilicate glass layer is generated on the front side of the silicon wafer. Therefore, it is necessary to remove the front phosphosilicate glass by single-sided etching, thereby reducing the recombination of electrons in the emission area and increasing the short-circuit current and open-circuit voltage.

[0123] In addition, if the polysilicon layer is prepared on both sides in step 201, before the passivation layer and the electrode are formed on the front side of the silicon wafer and the surface of the phosphorus-doped polysilicon layer in sequence, the front polysilicon layer needs to be etched with alkali or alkali + additive to remove the front polysilicon layer and retain the back polysilicon structure.

[0124] The acidic solution in the chain pickling is HF and / or HCl with a mass concentration of 1-3%, the alkaline solution is NaOH or KOH with a mass concentration of 5-10%, the alkali polishing reaction time is 280-300s, and the treatment temperature is 70-80°C, which can effectively remove the phosphosilicate glass on the front of the battery after phosphorus diffusion, reduce the recombination of electrons in the emission area, and improve the short-circuit current and open-circuit voltage.

[0125] Optionally, in one embodiment, in the above-mentioned laser-induced silver paste, the mass percentage of organic additives is 1 to 1.5%, the mass percentage of silver powder is 75 to 81%, the mass percentage of organic binder is 15.3 to 22.2%, and the mass percentage of glass powder is 1.8 to 2.2%, which can better match the light injection and laser induction effects and improve the photoelectric conversion efficiency of the battery.

[0126] Optionally, in one embodiment, the silver powder comprises 97-99% by mass of micron-sized spherical silver powder and 1-3% by mass of nano-sized spherical silver powder. Specifically, the silver powder comprises micron-sized spherical silver powder having a purity of 3 nines and a mass fraction of 97-99% and nano-sized spherical silver powder having a purity of 3 nines and a mass fraction of 2-5%. In the embodiment of the present invention, the silver powder is micron-sized spherical silver powder having a purity of 3 nines. Since there are gaps between micron-sized silver powders and gaps between micron-sized aluminum powders, the nano-sized spherical silver powder can just fill and penetrate into the gaps between the micron-sized silver powders.

[0127] Optionally, in another embodiment, the silver powder includes micron-sized spherical silver powder with a purity of 3 9s. That is, in this embodiment, the silver powder can be a single micron-sized silver powder.

[0128] Optionally, in one embodiment, the organic additive includes at least one of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.

[0129] In the preparation method provided in an embodiment of the present invention, the above-mentioned organic binder includes a high molecular polymer resin and an organic solvent; wherein the high molecular polymer resin is dissolved in the organic solvent, so that the organic solvent can serve as an organic binder, that is, the slurry plays the role of bonding the powder after drying.

[0130] Optionally, in one embodiment, the mass fraction of the high molecular weight polymer in the organic binder is 10-14%; the mass fraction of the organic solvent in the organic binder is 86-90%.

[0131] Optionally, in one embodiment, the high molecular weight polymer is one or more of ethyl cellulose-N20, ethyl cellulose N-50, and ethyl cellulose-N100;

[0132] The organic solvent includes at least four of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester 12.

[0133] Optionally, in one embodiment, the glass powder is obtained by sintering and crushing 10-20% Bi2O3, 10-15% Al2O3, 8-12% SiO2, 18-25% ZnO, 15-20% Sb2O5, 8-10% B2O3, and 15-20% TeO3 in mass percentages.

[0134] In this embodiment, the glass powder is obtained by sintering and crushing 10 to 20 parts of Bi2O3, 10 to 15 parts of Al2O3, 8 to 12 parts of SiO2, 18 to 25 parts of ZnO, 15 to 20 parts of Sb2O5, 8 to 10 parts of B2O3, and 15 to 20 parts of TeO3, by mass, wherein D50 of the glass powder is 2 to 2.5 μm. If D50 is less than 2 μm, the glass activity is too high, and if D50 is greater than 2.5 μm, the glass activity is too low.

[0135] Among them, Bi2O3 is the main network structure, ZnO can break the network structure and promote glass crystallization, Al2O3 can adjust the stability of the glass and increase the viscosity; SiO2 is used as a glass network former to promote glass stability and increase the glass melting point; Sb2O5 is used to clarify and uniform the glass liquid; B2O3 is a network body; and TeO3 lowers the glass formation temperature.

[0136] The present invention is described in detail below by way of examples.

[0137] Example 1

[0138] (1) Provide a single crystal N-type silicon wafer with a resistivity of 0.4Ω·cm, a size of 182×183.75mm, and a thickness of 180um, and place it in a texturing tank for single crystal alkaline texturing. The texturing tank contains 20 parts by volume of a 45% NaOH solution, 7 parts of a texturing additive, and 435 parts of water. The texturing time is controlled to be 270s and the temperature is controlled to be 65°C.

[0139] (2) The silicon wafer after texturing is sent into the furnace tube, and is first deposited for 580 seconds under the conditions of a temperature of 925°C, a BCl3 flow rate of 310 sccm, an oxygen flow rate of 870 sccm / min, a nitrogen flow rate of 3200 sccm / min, and a pressure of 150 mbar. Then, a picosecond laser is used to perform laser doping treatment at a power of 45 W and a speed of 30,000 mm / min. Then, a high-temperature annealing treatment is performed at a temperature of 450°C and an oxygen flow rate of 3000 sccm for 8 minutes. After the high-temperature annealing treatment is completed, the wafer is cooled and taken out of the boat;

[0140] (3) The non-diffusion surface of the silicon wafer after the boron doping treatment is etched by chain HF and HCl single-side etching to remove the borosilicate glass layer, and a square morphology structure is formed by alkali polishing; wherein the HF concentration is 2wt% and the HCl concentration is 1.8wt%; the solution used for the alkali polishing treatment includes 18 parts by volume of a 45% NaOH solution, 7 parts of an alkali polishing additive BP52, and 460 parts of water, and the alkali polishing treatment time is controlled to be 275s and the temperature is controlled to be 75°C;

[0141] (4) First, grow an ultra-thin oxide layer with a thickness of 1.5nm on the back side, and then prepare a polysilicon layer with a thickness of 150nm on both sides; put the silicon wafer into the furnace tube, and deposit the silicon wafer for 10 minutes under the conditions of a temperature of 900℃, a phosphorus source including POCl3 with a flow rate of 130sccm / min, an oxygen flow rate of 700sccm / min, a nitrogen flow rate of 1800sccm / min, and a pressure of 170mbar; then heat the silicon wafer to 960℃, control the pressure to 920mbar, and treat it for 50 minutes with an oxygen flow rate of 10000sccm / min;

[0142] (5) first remove the front phosphosilicate glass by single-sided acid etching, and then remove the front polysilicon layer by alkaline etching; wherein, the solution in the acid etching treatment is 2wt% HF and 1.5wt% HCl, and the solution used in the alkaline etching treatment includes 28 parts by volume of 45% NaOH solution, 4.5 parts of texturing additive BP65, and 465 parts of water, and the alkaline etching treatment time is controlled to be 260s and the temperature is 70°C;

[0143] (6) Depositing an aluminum oxide layer as a passivation layer on the front side of the silicon wafer, and sequentially depositing SiNx layers on the front side and back side as anti-reflection layers, wherein the thickness of the aluminum oxide layer is 3 nm, and the thickness of the SiNx layer is 75 nm; the deposition temperature of the aluminum oxide layer is 250°C, and the deposition time is 8 min; the deposition temperature of the SiNx layer is 600°C, and the deposition time is 6 min;

[0144] (7) preparing a front fine grid by screen printing a laser-induced silver paste with a thickness of 19 μm through 520 mesh, and then sintering at 736° C. wherein, by weight, the silver paste consists of 1.2 parts of an organic additive, 80 parts of silver powder, 16.8 parts of an organic binder, and 2 parts of glass powder;

[0145] The organic additive is a silane coupling agent; the silver powder comprises micron-grade silver powder with a purity of 3 9s; the organic binder comprises 10% by mass of ethyl cellulose-N100 and 90% by mass of an organic solvent, wherein the organic solvent is composed of benzyl alcohol, diethyl phthalate, terpineol, tributyl citrate, Span 85, and alcohol ester twelve; the glass powder is obtained by sintering and crushing 18% by mass of Bi2O3, 10% by mass of Al2O3, 12% by mass of SiO2, 18% by mass of ZnO, 15% by mass of Sb2O5, 8% by mass of B2O3, and 19% by mass of TeO3 to obtain the glass powder, wherein the D50 thereof is 2 to 2.5 μm;

[0146] (8) Place the cell at 526°C and a light intensity of 6500w / m 2 Light injection treatment was performed for 3s under the conditions of

[0147] (9) After light injection, the cell is passed through a laser device to perform laser irradiation and deflection voltage treatment on the fine grid on the front side of the silicon wafer; wherein the direction of the electric field formed by the deflection voltage is opposite to the direction of the electric field built into the N-type TOPCon cell, the laser power is 12W, the reverse voltage intensity is 42V, and the application time is 0.3s;

[0148] (10) Take the laser-induced solar cell and perform laser grooving on the back side. The laser uses a green picosecond laser with a laser power of 6W. The laser grooving depth is 120nm and the width is 25 microns.

[0149] (11) Depositing ITO with a thickness of 180 nm on the back of the groove to form a first conductive layer;

[0150] (12) A layer of NiO and PVK is prepared on the prepared first conductive layer to form a hole transport layer with a thickness of 25 nm;

[0151] (13) A layer of CH3NH3PbCl3 was prepared on the prepared hole transport layer to form a perovskite layer with a thickness of 350 nm;

[0152] (14) A layer of C60 was prepared by thermal evaporation on the prepared perovskite layer as an electron transport layer with a thickness of 35 nm;

[0153] (15) A dense ZnO layer was deposited by atomic layer deposition as a conductive transition layer with a thickness of 120 nm;

[0154] (16) Depositing ITO on the conductive transition layer to form a second conductive layer with a thickness of 250 nm;

[0155] (17) Printing low-temperature conductive silver paste on the second conductive layer by screen printing to form a backside fine grid;

[0156] (18) Welding the front fine grid and the back fine grid to the first welding strip and the second welding strip respectively to produce a solar cell.

[0157] Example 2

[0158] The difference between Example 2 and Example 1 is that in step (7), the silver paste is adjusted to consist of 1 part of an organic additive, 75 parts of silver powder, 22.2 parts of an organic binder and 1.8 parts of a glass powder, and the sintering temperature is adjusted to 735°C; wherein the organic additive is a silane coupling agent; the silver powder comprises a micron-grade silver powder with a purity of 3 9s; the organic binder comprises 12% by mass of ethyl cellulose-N100 and 88% by mass of an organic solvent, wherein the organic solvent is composed of benzyl alcohol, diethyl phthalate, terpineol, tributyl citrate, Span 85 and alcohol ester twelve; the glass powder is sintered and crushed to obtain a glass powder with a D50 of 2 to 2.5 μm by weight of 10% Bi2O3, 10% Al2O3, 12% SiO2, 20% ZnO, 18% Sb2O5, 10% B2O3 and 20% TeO3;

[0159] In steps (11) to (16), the thickness of the first conductive layer is adjusted to 160 nm, the thickness of the second conductive layer is adjusted to 220 nm, the thickness of the conductive transition layer is adjusted to 100 nm, the thickness of the hole transport layer is adjusted to 20 nm, the thickness of the perovskite layer is adjusted to 200 nm, and the thickness of the electron transport layer is adjusted to 20 nm.

[0160] Example 3

[0161] The difference between Example 3 and Example 1 is that in step (7), the silver paste is adjusted to consist of 1.5 parts of organic additives, 81 parts of silver powder, 15.1 parts of organic binder and 2.2 parts of glass powder, and the sintering temperature is adjusted to 738°C; wherein the above-mentioned organic additive is a silane coupling agent; the silver powder includes micron-grade silver powder with a purity of 3 9s; the organic binder includes 12% by mass of ethyl cellulose-N100 and 88% by mass of an organic solvent, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, terpineol, tributyl citrate, Span 85 and alcohol ester twelve; the glass powder is sintered and crushed to obtain glass powder with a D50 of 2 to 2.5 μm by weight of 10% Bi2O3, 10% Al2O3, 12% SiO2, 20% ZnO, 18% Sb2O5, 10% B2O3 and 20% TeO3;

[0162] In steps (11) to (16), the thickness of the first conductive layer is adjusted to 210 nm, the thickness of the second conductive layer is adjusted to 280 nm, the thickness of the conductive transition layer is adjusted to 150 nm, the thickness of the hole transport layer is adjusted to 30 nm, the thickness of the perovskite layer is adjusted to 500 nm, and the thickness of the electron transport layer is adjusted to 50 nm.

[0163] Example 4

[0164] The difference between Example 4 and Example 1 is that in step (8), the light injection temperature is adjusted to 500°C and the light intensity is adjusted to 5000w / m 2 ;

[0165] In step (9), adjust the laser power to 10W, the reverse voltage intensity to 30V, and the application time to 0.2s.

[0166] Example 5

[0167] The difference between Example 5 and Example 1 is that in step (8), the light injection temperature is adjusted to 600°C and the light intensity is adjusted to 8000w / m 2 ;

[0168] In step (9), adjust the laser power to 15W, the reverse voltage intensity to 60V, and the application time to 0.5s.

[0169] The solar cells prepared in Examples 1 to 5 were subjected to electrical performance IV tests, and the results are shown in Table 1.

[0170] Table 1

[0171]

[0172] To sum up, in this embodiment, the stacked perovskite cell structure is arranged on the back of the N-type TOPCon cell structure through the connection of the first conductive layer, and the boron-doped region in contact with the fine grid on the front of the N-type TOPCon cell structure is doped with a high concentration, and the main grid is omitted. This not only ensures the advantage of the smaller attenuation of the N-type TOPCon cell and improves the photoelectric conversion efficiency of the N-type TOPCon cell, but also effectively reduces the impact of ultraviolet and infrared on the perovskite cell, and achieves the effect of higher photoelectric conversion efficiency of the perovskite cell structure, and increases the effective utilization area of ​​the cell, so that the formed solar cell effectively takes into account both photoelectric conversion efficiency and reliability.

[0173] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0174] The above is a detailed introduction to a solar cell and a method for preparing the same provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the contents of this specification should not be understood as limiting the present invention.

Claims

1. A solar cell, characterized in that: It includes a first welding ribbon, a solar cell sheet and a second welding ribbon; The solar cell comprises, from the front side to the back side, a front fine grid, a first anti-reflection layer, a passivation layer, a boron-doped layer, an N-type silicon wafer, a tunneling oxide layer, a phosphorus-doped polysilicon layer, a second anti-reflection layer, a first conductive layer, a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer, and a back fine grid, wherein the front fine grid contacts the boron-doped layer and is welded to the first welding ribbon, the first conductive layer contacts the phosphorus-doped polysilicon layer, and the back fine grid is welded to the second welding ribbon; The boron-doped layer includes a first boron-doped region and a second boron-doped region. The first boron-doped region is used to contact the front fine gate. The second boron-doped region is other regions in the boron-doped layer except the first boron-doped region. The boron doping concentration of the first boron-doped region is higher than the boron doping concentration of the second boron-doped region.

2. The solar cell according to claim 1, wherein The first passivation layer includes an aluminum oxide layer, and the first anti-reflection layer and the second anti-reflection layer include silicon nitride layers.

3. The solar cell according to claim 1, wherein The first conductive layer and the second conductive layer are both indium oxide layers; and / or The conductive transition layer is a zinc oxide layer; and / or The hole transport layer comprises NiO and PVK; and / or The material of the perovskite layer is CH3NH3PbCl3; and / or The material of the electron transport layer is C60.

4. The solar cell according to claim 1, wherein The thickness of the first conductive layer is 160 to 210 nm; and / or The thickness of the second conductive layer is 220-280 nm; and / or The thickness of the conductive transition layer is 100 to 150 nm; and / or The thickness of the hole transport layer is 20 to 30 nm; and / or The thickness of the perovskite layer is 200 to 500 nm; and / or The thickness of the electron transport layer is 20 to 50 nm.

5. A method for preparing a solar cell, characterized in that: include: After performing boron diffusion and laser doping on the front side of an N-type silicon wafer and sequentially forming a tunneling oxide layer and a phosphorus-doped polysilicon layer on the back side, a passivation layer is formed on the front side of the silicon wafer, and an anti-reflection layer is formed on the front side of the silicon wafer and on the surface of the phosphorus-doped polysilicon layer; Printing laser-induced silver paste on the front surface to form a front fine grid, wherein the laser-induced silver paste comprises components including organic additives, silver powder, organic binder and glass powder; The silicon wafer with the front and back fine grids formed thereon is subjected to light injection treatment, and the front fine grid of the silicon wafer after the light injection treatment is subjected to laser irradiation and deflection voltage treatment, wherein the direction of the electric field formed by the deflection voltage is opposite to the direction of the electric field built into the silicon wafer; After laser irradiation and deflection voltage treatment, a first conductive layer conductive to the phosphorus-doped polysilicon layer is deposited on the back surface, and a hole transport layer, a perovskite layer, an electron transport layer, a conductive transition layer, a second conductive layer and a back fine grid are sequentially formed on the first conductive layer; The front fine grid is welded to a first welding strip, and the back fine grid is welded to a second welding strip to manufacture a solar cell.

6. The preparation method according to claim 5, characterized in that Before sequentially forming a tunnel oxide layer and a phosphorus-doped polysilicon layer on the back side, the method further includes: The silicon wafer after the laser doping treatment is subjected to oxidation annealing treatment.

7. The preparation method according to claim 5, characterized in that In the laser-induced silver paste, the mass percentage of the organic additive is 1-1.5%; the mass percentage of the silver powder is 75-81%; the mass percentage of the organic binder is 15.3-22.2%; and the mass percentage of the glass powder is 1.8-2.2%.

8. The preparation method according to claim 5, characterized in that Forming the back side fine grid specifically includes: A low-temperature conductive silver paste is printed on the second conductive layer.

9. The preparation method according to any one of claims 5 to 8, characterized in that During light injection treatment, the light intensity is 5000~8000W / m 2 .

10. The preparation method according to any one of claims 5 to 8, characterized in that: In the laser irradiation and deflection voltage treatment, the laser power is 10 to 15 W, the voltage intensity is 30 to 60 V, and the application time is 0.2 to 0.5 s.